Spectroscopic and Nonlinear Optical Investigations of Nitroisoxazoles: Host-Guest Interactions with β-cyclodextrin and Dft-Supported Stability Analysis - Martinez-Gomez, F (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Six vinyl-functionalized nitroisoxazole derivatives (A1-A6) were synthesized and structurally characterized, including the first report of compound A6. Their inclusion complexation with beta-cyclodextrin (beta-CD) was investigated using UV-Vis spectroscopy, 1H NMR (including T1 and T2relaxation times), and thermodynamic analyses. Complex formation was confirmed using Job s and Benesi-Hildebrand methods, with spontaneous binding observed across the series (Delta G:-3.73-4.01 kcal/mol). A3 (piperidine) and A2 (pyrrolidine) exhibited the highest affinities, which were predominantly driven by entropic and enthalpic contributions, respectively. NMR data supported the axial insertion of the isoxazole moiety through the wider rim of (3-CD in all cases. The electronic and nonlinear optical (NLO) properties of the free compounds were evaluated via DFT (M06-2x/ 6-311++G(d,p)), revealing that heterocyclic substituents modulate electron affinity and electrophilicity. All the derivatives displayed promising NLO responses, highlighting their potential for optoelectronic material design. The cytotoxicity assays in Vero cells showed low toxicity at 400 mu M for all compounds, which further decreased upon (3-CD encapsulation. These findings demonstrated that (3-CD complexation can effectively modulate the physicochemical, optical, electronic, and biological properties of nitroisoxazoles, supporting their application in supramolecular systems and functional optical materials.